DETERMINATION OF EFFECTS OF CHEMICAL ADDITIVES ON GYPSE BINDER FROM INDUSTRIAL WASTE PHOSPHOGYPSUM - NURMUKHAMEDOV SANJARBEK ILKHAMOVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article discusses the methods of obtaining gypsum binder from industrial waste, the physical and mechanical properties of industrial waste phosphogypsum. They are different. It is planned to create a wide range of opportunities for the creation of building materials from industrial waste in the future, as well as to compare their advantages and disadvantages.